Population-based incidence and epidemiology of 5912 foot fractures. Issue 2 (February 2021) - Rasmussen, Christian G.; Jørgensen, Søren B.; Larsen, Peter; Horodyskyy, Mykola; Kjær, Inge L.; Elsoe, Rasmus
Highlights: Foot fracture incidence is 142.3/100, 000/year. Hind foot incidence: 13.7, mid foot 6.5 and fore foot 123.9/100, 000/year. Both genders showed a peak incidence in the age group 10–19 years. Low energy trauma was the most common mode of injury (98.7%). Abstract: Background: The present study aimed to report a full overview of the incidence and epidemiology of foot fractures. Method: Population-based epidemiological cohort study including all foot fractures over 5 years. All patient charts and radiology were manually assessed. Results: A total of 4938 patients sustained 5912 foot fractures during the study period. Patients' mean age at the time of fracture was 36.1 (21.7 SD) years. The overall incidence of foot fractures was 142.3/100, 000/year. The hind foot incidence was 13.7/100, 000/year, the mid foot incidence 6.5/100, 000/year, and the fore foot incidence 123.9/100, 000/year. The most common mode of injury was due to low energy trauma (98.7%). Conclusion: This study shows an overall incidence of foot fractures to be 142.3/100, 000/year. The hind foot incidence is 13.7/100, 000/year, the mid foot incidence 6.5/100, 000/year, and the fore foot incidence 123.9/100, 000/year.